FACTORS AFFECTING THE PURCHASING DECISION FACIAL SKINCARE PRODUCTS OF WORKING WOMEN IN BANGKOK METROPOLIS DURING ECONOMIC RECESSION PERIOD - Boonmangmee, Pusanisa; Methavasaraphak, Preecha (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Abstract: The facial skincare products were in group of convenience goods that customers would buy from their wanted not needed so can said that facial skincare products were unnecessary for life. However, the competition in the skincare business was very high. Consumer had a lot of choices to select. This research aimed to study about factors related and affecting purchasing decision facial skincare products of working women in Bangkok Metropolis during Economic Recession Period. The quantitative questionnaires were conducted and also distributed 400 sets of questionnaires to working women who worked or lived in Bangkok, Thailand which were ever bought facial skincare product within 10 months ago. The Statistical Package for Social Science (SPSS) were used to analyze the data there is three analyses which are descriptive analysis (frequency, mean and standard deviation), correlation analysis and multiple regression analysis. Literature review shown in six factors might be related and affected on purchasing decision consist of product quality, convenience place, promotion, brand, self-image and social norms. After analysis by descriptive analysis and multiple linear regression the result shown only two factors related and affect purchasing decision facial skincare products of working women in Bangkok Metropolis during Economic Recession Period that were product quality and brand. Which can explain that 36.9% (R2=.369) of the variation affect in purchasing decision facial skincare products of working women in Bangkok Metropolis during economic recession period. Others factors consist of convenience place, promotion, self-image and social norms did not had statistic significantly on purchasing decision of working women in Bangkok.